Analisis Makna Dalam Lirik Lagu Masa Mudaku Habis Karya Ghea Indrawari: Kajian Semiotika Rholand Barthes - Kartika, Yunda; Edria, Ade Lola; Ibrahim, Dimas; Ningsih, Mutiara Umami; Pranata, Jaya Reza (Jurnal Ilmiah Wahana Pendidikan, 2024)
Abstract Received: Revised: Accepted: This research discusses the meaning of denotation, connotation and myth in the lyrics of the song "Masa Mudaku Habis" which was popularized by Ghea Indrawari in 2023. This song describes the exploration of a person's emotions when they have entered the adult phase, as well as about a person's sadness and nostalgia when they realize that time is running out. passed and his youth had passed. Researchers chose this song for analysis because the song's lyrics are very touching and match the reality of life that happens to each person. By using the concept that song lyrics are a representation of emotional feelings (longing) that have a message, this research seeks to find out what the denotative, connotative and mythical meanings are in the song lyrics. This research uses a descriptive qualitative approach and Roland Barthes' semiotic analysis method in dissecting and studying the song's lyrics.